Voluntary industrial aid : inter-departmental correspondence - Bunn, C. S.
036-0044-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From C.S. Bunn Department Secretary's To Miss McDONALD Date 12th April, 1937. SUBJECT. VOLUNTARY INDUSTRIAL AID. This is one of the matter on which Mr. Tewson had been anxious to see Sir Walter, but whether he had any conversation with him, I do not know. See Report of interview with Mr. Pyke. Mr. Middleton has had a letter, asking for an interview, and has been given a copy of Mr. Tewson's interview with Mr. Pyke. C.S.B. Please let Mr Scott know when Sir Walter has taken a decision 292/946/36/44